2019
DOI: 10.1002/cne.24810
|View full text |Cite
|
Sign up to set email alerts
|

Increased density and age‐related sharing of synapses at the cone to OFF bipolar cell synapse in the mouse retina

Abstract: Neural circuits in the adult nervous system are characterized by stable, cell type‐specific patterns of synaptic connectivity. In many parts of the nervous system these patterns are established during development through initial over‐innervation by multiple pre‐ or postsynaptic targets, followed by a process of refinement that takes place during development and is in many instances activity dependent. Here we report on an identified synapse in the mouse retina, the cone photoreceptor➔type 4 bipolar cell (BC4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…We were able to measure BC3bs at the dendrite point before branching, which is a smaller space than the soma and could be offset from the soma due to dendritic tiling. This would suggest that factors that mediate spacing of BCs could promote dendrite spacing but not soma spacing, consistent with the localization of DSCAM protein, which regulates OFF BC tiling, on the dendrite tips of these cells (Simmons et al, 2017; Simmons et al, 2020).…”
Section: Discusionmentioning
confidence: 58%
“…We were able to measure BC3bs at the dendrite point before branching, which is a smaller space than the soma and could be offset from the soma due to dendritic tiling. This would suggest that factors that mediate spacing of BCs could promote dendrite spacing but not soma spacing, consistent with the localization of DSCAM protein, which regulates OFF BC tiling, on the dendrite tips of these cells (Simmons et al, 2017; Simmons et al, 2020).…”
Section: Discusionmentioning
confidence: 58%
“…Second, we compared cells from retinas that lack the pro‐apoptotic gene Bax to those from WT littermates. Many cell types have elevated numbers in these Bax knockout (KO) retinas, including the rod bipolar cells (Simmons et al, 2019 ). The thickness of the ONL and OPL remains unchanged (Lee et al, 2011 ; Péquignot et al, 2003 ), however, suggesting that rod photoreceptor number is unaltered; indeed, we found that counts of rod photoreceptors do not significantly differ in the absence of Bax (WT: mean ± SEM = 7,625,975 ± 188,281, n = 3; KO: mean ± SEM = 7,913,681 ± 198,660, n = 3; p = 0.353).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, these lines do not faithfully recapitulate the endogenous distribution of the HTR2A as has been seen with other BAC-transgenic mice (Matthaei, 2007). Despite this limitation, some groups have been used for HTR2-related research, such as electrophysiological studies (Weber et al, 2010), retina-related studies (Simmons et al, 2020)and circuitry-related research. The resultant data should be interpreted with caution since the distribution of HTR2A in the Htr2a BAC mouse lines are distinct from that of the endogenous receptor based on studies using receptor autoradiography (Pazos et al, 1985; Roth et al, 1987), immunohistochemistry (Willins et al, 1997a; Backstrom et al, 1997; Miner et al, 2003; Mengood et al, 1990), in situ hybridization (Wright et al, 1995) and our mouse lines.…”
Section: Discussionmentioning
confidence: 99%